Kirsten saves the day : a summer story - Shaw, Janet Beeler, 1937- (American girls collection., 1988)
Ten-year-old Kirsten is proud and excited when she finds a bee tree full of honey, one of the natural treasures of her Minnesota frontier world, but she exposes herself to great danger by trying to harvest the honey by herself.